2005
DOI: 10.1021/bi050499f
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Studies of A-to-I Editing by tRNA:A34 Deaminases at the Wobble Position of Transfer RNA,

Abstract: Initial RNA transcription produces several tRNAs (one in prokaryotes and plant chloroplasts and seven or eight in eukaryotes) that contain an adenosine (A) at the wobble position (position 34). However, in all cases, adenosine at position 34 is post-transcriptionally converted to inosine (I), producing mature tRNAs without adenosine at the wobble position. The enzymes responsible for this A-to-I conversion in tRNA are tadA (acting as a homodimer) in prokaryotes and the heterodimeric ADAT2-ADAT3 complex in euka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 35 publications
7
64
0
Order By: Relevance
“…Currently, however, nothing is known about the mode of tRNA binding by any of the eukaryotic tRNA deaminases, so it is not clear if similar sequences found at the C terminus of other ADAT2s may provide a tRNA binding function. The data presented support a previous model in which, through evolution and in order to accommodate many different substrates, a domain has been appended away from the enzyme's active site, providing critical substrate binding functions (Elias and Huang 2005).…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…Currently, however, nothing is known about the mode of tRNA binding by any of the eukaryotic tRNA deaminases, so it is not clear if similar sequences found at the C terminus of other ADAT2s may provide a tRNA binding function. The data presented support a previous model in which, through evolution and in order to accommodate many different substrates, a domain has been appended away from the enzyme's active site, providing critical substrate binding functions (Elias and Huang 2005).…”
Section: Introductionsupporting
confidence: 81%
“…Given the remarkable catalytic flexibility of the TbADAT2/3 (able to perform both A to I and C to U editing in vitro) (Rubio et al 2007), our work has concentrated on utilizing this enzyme to explore its mode of tRNA binding. We have demonstrated that, as predicted by Huang and coworkers, the C-terminal end of ADAT2 contains an essential domain for tRNA binding (Elias and Huang 2005). This domain is formed by a string of positively charged amino acids (arginines and lysines) we termed the KR-domain.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…One key difference that emerged was the presence of the additional ␣-helix 3 between ␤-strands 4 and 5 in APOBEC proteins, which is absent from the nucleotide cytidine deaminases. Based on the crystal structures of the human adenosine-to-inosine editing enzyme ADAR2 (29), the tRNA adenosine deaminases from Aquifex aeolicus (15,25) and Staphylococcus aureus (27), Saccharomyces cerevisiae cytosine deaminase (23,24), and APOBEC2 (an orphan APOBEC family member whose crystal structure was reported while this work was being reviewed) (41), it is now believed that ␣-helix 3 of APOBEC protein CDA cores crosses the ␤-sheet, resulting in a parallel positioning of ␤-strands 4 and 5. As a consequence, this helix is located toward the same face of the ␤-sheet as helices ␣1 and ␣2 (Fig.…”
Section: Resultsmentioning
confidence: 99%